Traveler’s Infections: Understanding SARS-CoV-2 as a Potential Agent - Oti, Victor Baba; Ioannou, Marina (UI Scholars Hub, 2020)
Coronavirus disease 2019 (COVID-19) has become a major, global, public health challenge. Over 1,051,635 confirmed cases have been reported worldwide, and both local and international travelers are considered to represent populations at high risk of acquiring the infection. Many factors are involved in the spread of this viral agent, including travel to and from endemic areas, a history of contact with a traveler from an endemic country, the virus infection rate at the destination, individual health, and inadequate prevention and control measures. The virus is thought to be transmitted through respiratory droplets, generated by coughing or sneezing and spread through close contact with infected persons or contaminated surfaces. Diagnostic strategies include detection of antiviral antibodies, multiplex nucleic acid amplification, and microarray-based assays. Currently, no approved antiviral therapy or vaccine exists to treat or prevent the infection. Public health measures have been enforced, to slow spread of the virus, by governments. The World Health Organization (WHO) have recommended screening be performed at airports, for all travelers, before traveling to endemic countries and the restriction of travel to countries more than one thousand cases of infection. In response to the global outbreak, this review examines COVID-19 as a potential traveler’s infection.